Assessment of Stress Levels in Patients Visiting for Dental Treatment. - Sinha, Pallavi; Raju, Veena; Jandrajupalli, Suresh Babu; Chandolu, Swarnalatha; Karan, Abhishek; Nayyar, Abhishek Singh (Biology, Engineering, Medicine and Science Reports)
Introduction: The perception of stress might have a multifactorial influence on a disease pro- cess. Surprisingly, this theoretical perspective has not been discussed in the context of odon- togenic problems. Materials and Methods: Hence this cross-sectional study was planned en- rolling individuals randomly selected from the Outpatient Department aged over 18 years for duration of 6 months. Perceived Stress Scale (PSS) was used to measure perception of stress. The data was analyzed using Chi-square/Fisher’s exact test in SPSS version 15.0 (SPSS Inc., Chicago, IL, USA). Results: Our data indicated that unskilled individuals (29.4%) sought dental treatment more frequently than the other categories of occupational groups included in this study. Patients with Oral submucous fibrosis (OSF) and lichen planus showed relatively higher stress levels compared to patients with other dental conditions. A correlation analysis showed that stress levels were considerably lower in patients from professional category than in the non-professional groups, emphasizing the significance of education and professional status on the perception of stress in individuals. Conclusion: Based on this study findings it can be con- cluded that nature of the dental problem and the education and professional status of patients can differentially impact the perception of stress among outpatients seeking dental treatment.
Keywords: Stress levels; Patients; Dental treatment; Perceived Stress Scale (PSS); Physi- ological processes; Psychological stress; Perceived stress; Psychological distress; Physical disorder; Disease states; Questionnaire study